A Production Service Management Model using Lean Tools to Increase Productivity in an Agro-Export Company - Ramos-Leon, Heissell (2023)
The growth of Peruvian exports has been remarkable in the last two decades, and especially in non-traditional products, which include vegetables, cereals, and fruit, among others. The industries dedicated to processing these products often report large food losses during their production process, which translates into low productivity rates. For this reason, this research study develops a Production Management model to address this problem and improve conditions through a model that fosters Continuous Improvement. This includes the implementation of Lean tools such as Work Standardization and an organization model based on the 5S. Likewise, the Systematic Layout Planning (SLP) method is applied to determine the spaces of problem areas. For this study, the processing of frozen mango was assessed and the causes that generate the low productivity issues were identified. Based on this, the processes are evaluated, and the corresponding solutions are determined. After the implementation of the model, productivity increased to 74%, waiting times were reduced to 24 minutes, and the total distance traveled was reduced by 32 meters.